2013
DOI: 10.1002/cncr.27951
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of preoperative image‐guided intensity‐modulated radiation therapy to reduce wound and combined modality morbidities in lower extremity soft tissue sarcoma

Abstract: BACKGROUND: This study sought to determine if preoperative image‐guided intensity‐modulated radiotherapy (IG‐IMRT) can reduce morbidity, including wound complications, by minimizing dose to uninvolved tissues in adults with lower extremity soft tissue sarcoma. METHODS: The primary endpoint was the development of an acute wound complication (WC). IG‐IMRT was used to conform volumes to avoid normal tissues (skin flaps for wound closure, bone, or other uninvolved soft tissues). From July 2005 to June 2009, 70 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(151 citation statements)
references
References 29 publications
6
139
1
3
Order By: Relevance
“…Intensity Modulated Radiotherapy (IMRT) permits dose contouring to enable accurate targeting of tumor cells whilst minimizing dose to uninvolved tissues. A recent large prospective phase-II clinical trial demonstrated no difference in total wound complications as compared with EBRT but of interest it did show a 0% fracture rate in long bone STS [10]. As of yet, there have been no comparative studies of EBRT and IMRT; thus, the potential advantages of IMRT remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity Modulated Radiotherapy (IMRT) permits dose contouring to enable accurate targeting of tumor cells whilst minimizing dose to uninvolved tissues. A recent large prospective phase-II clinical trial demonstrated no difference in total wound complications as compared with EBRT but of interest it did show a 0% fracture rate in long bone STS [10]. As of yet, there have been no comparative studies of EBRT and IMRT; thus, the potential advantages of IMRT remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…More recently reported experiences with the use of preoperative EBRT with modern RT techniques show more favourable results in terms of complications, and IORT boost remains a very favourable option when critical, positive or close surgical margins are expected. Preoperative EBRT and IORT boost should be considered in particular when reconstructive surgery with flaps is needed, because of the possibility of sparing the vulnerable reconstruction and avoiding postoperative EBRT [14].…”
Section: Against Iortmentioning
confidence: 99%
“…If daily image guidance with cone beam or MV-CT is performed, a 0.5 cm CTV expansion for the PTV is permitted (O'Sullivan et al 2013 ).…”
Section: Ests Target Volume Delineation For Preoperative Radiotherapymentioning
confidence: 99%